Ovarian Mature Cystic Teratoma: Challenges of Surgical Management - Abha Sinha; Ayman A. A. Ewies (Obstetrics and Gynecology International)
Although ovarian mature cystic teratomas are the commonest adnexal masses occurring in premenopausal women, there are many challenges faced by gynecologists on deciding upon the best surgical management. There is uncertainty, lack of consensus, and variation in surgical practices. This paper critically analyzes various surgical approaches and techniques used to treat these cysts in an attempt to outline a unified guidance. MEDLINE and EMBASE databases were searched in January 2015 with no date limit using the key words “ovarian teratoma” and “ovarian dermoid.” The search was limited to articles in English language, humans, and female. The two authors conducted the search independently. The laparoscopic approach is generally considered to be the gold standard for the management. Oophorectomy should be the standard operation except in younger women with a single small cyst. The risk of chemical peritonitis after contents spillage is extremely rare and can certainly be overcome with thorough peritoneal lavage using warmed fluid. There is a place for surveillance in some selected cases.